Sarcopenia from Pathophysiology to Clinical : Literature Review - Rachmat Hidayat; Nur Riviati (Biomedical Journal of Indonesia, 2021)
The causes of sarcopenia are thought to be multifactorial including: environmental factors, illness, activation of inflammatory pathways, mitochondrial dysfunction, loss of neuromuscular junctions, reduced number of satellite cells and changes in the quality of hormonal function. The mechanism of sarcopenia occurs because the aging process coupled with reduced physical activity can cause the formation of cytokines to increase so that inflammation is easy, insulin resistant, anabolic resistance and neuromuscular impairments.